Elliptical applicator design through analysis, modelling and material property knowledge - Fouche, Carien (Stellenbosch : University of Stellenbosch, 2008)
The properties of an elliptical microwave applicator are investigated. The investigation includes the analytical solution of the cutoff frequencies and electromagnetic field patterns in elliptical waveguides. This requires the solution of Mathieu Functions and becoming familiar with an orthogonal elliptical coordinate system. The study forms part of a wider investigation into the microwave heating of minerals and a cavity is designed in such a way that modes are produced at 896MHz. Extensive use is made of simulation packages. These software packages require that the user knows the dielectric properties of materials that are part of simulations. Therefore, the determination of these properties through measurement and the use of genetic algorithms is considered. A method to improve an S-band waveguide measurement system by implementing time domain gating and an offline calibration code previously written forms an integral part of this section of the project. It is found that, within limits, elliptical waveguides tend to produce a greater number of modes within a certain frequency range when compared to rectangular waveguides.